2014
DOI: 10.14393/rbcv66n3-44762
|View full text |Cite
|
Sign up to set email alerts
|

Aplicação E Avaliação Do Modelo De Previsão Numérica Do Tempo Eta15km No Posicionamento Absoluto

Abstract: As tecnologias espaciais têm sido amplamente empregadas para fins de posicionamento, a principal e mais moderna é o GNSS (Global Navigation Satellite System). Para alcançar alta acurácia (centímetros) no posicionamento GNSS, é imprescindível realizar a modelagem atmosférica (ionosfera e troposfera). No que concerne à troposfera, seus efeitos nos sinais GNSS são modelados considerando duas componentes: a primeira gerada pela influência hidrostática representa cerca de 90% do efeito; a segunda ocasionada pela at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In Brazil, some research carried out on the impacts of tropospheric models on GNSS positioning can be highlighted, such as those by Gouveia et al (2014), Cherubim et al (2016, Abreu et al (2014), Oliveira et al (2014) and Alves et al (2016). Among the most recent studies carried out in other countries, involving evaluation of tropospheric models in PPP, we can highlight the work carried out by Wang & Li (2016), Pan & Guo (2018), Xiong et al (2019) and Tunali & Ozludemir (2019).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…In Brazil, some research carried out on the impacts of tropospheric models on GNSS positioning can be highlighted, such as those by Gouveia et al (2014), Cherubim et al (2016, Abreu et al (2014), Oliveira et al (2014) and Alves et al (2016). Among the most recent studies carried out in other countries, involving evaluation of tropospheric models in PPP, we can highlight the work carried out by Wang & Li (2016), Pan & Guo (2018), Xiong et al (2019) and Tunali & Ozludemir (2019).…”
Section: Introductionmentioning
confidence: 89%
“…In Abreu et al (2014) was evaluated and quantified the wet component of the tropospheric delay in different regions of Brazil using RBMC data. It was observed that the highest values of ZWD were obtained at the SAGA station and the lowest at the UFPR station.…”
Section: Introductionmentioning
confidence: 99%